Impact of Exclusively Administered Hindmilk-Rich Feeds on Weight Gain in Preterm Neonates - Surya Vaishnavi, J; Arunkumar, R. (Journal of Neonatal Surgery, 2025)
Introduction:Preterm and low-birth-weight (LBW) neonates are at heightened risk of growth failure and neonatal morbidity due to immature gastrointestinal systems and high metabolic demands. Human breast milk, particularly hindmilk, is rich in fat and calories and may enhance early postnatal growth. This study aimed to evaluate the impact of hindmilk feeding on the growth parameters of preterm neonates compared to standard composite milk feeding. Materials and Methods:A prospective observational study was conducted over 12 months (January–December 2024) in the Department of Pediatrics at a tertiary care hospital in Kanchipuram. A total of 100 preterm neonates (<37 weeks gestation, <2500 grams) without clinical complications were enrolled and randomly assigned to two groups. Group 1 (n = 50) received exclusively expressed hindmilk; Group 2 (n = 50) received composite milk feeds. Daily weight and weekly head circumference and length were measured for two weeks or until discharge. Data were analyzed using SPSS Version 20.0, with p < 0.05 considered statistically significant. Results:At baseline, both groups were comparable in admission weight and APGAR scores. However, Group 1 neonates had slightly lower gestational age, head circumference, and length. By discharge, the hindmilk group showed significantly greater improvements in weight (p = 0.02), head circumference (p = 0.04), and length (p = 0.001) compared to the composite milk group. Subgroup analysis also revealed enhanced growth in neonates between 28–32 weeks gestation in the hindmilk group. Conclusion:Hindmilk feeding significantly improved early growth outcomes in preterm and LBW neonates, supporting its role as a practical and safe nutritional strategy. Promoting maternal education and implementing hindmilk-focused feeding protocols in NICUs may contribute to better neonatal health and development